Release of a guest by disassembling a capsule through a photo triggering process - Nithyanandhan, Jayaraj; Jagadesan, P.; Samanta, S. R.; Da Silva, J. P.; Ramamurthy, V. (Organic Letters, 2015)

Effect of out-of-plane alkyl group's position in dye-sensitized solar cell efficiency: a structure-property relationship utilizing indoline-based unsymmetrical squaraine dyes - Alagumalai, Ananthan; Fairoos, Munavvar M. K.; Vellimalai, Punitharasu; Sil, Manik Chandra; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2016)
Squaraine dyes are promising chromophores to harvest visible and near-infrared (NIR) photons. A series of indoline-based unsymmetrical squaraine (SQ) dyes that contain alkyl chains at sp(3) C- and N- atoms of indoline moieties with a carboxylic acid anchoring group were synthesized. The optical and electrochemical properties of the SQ dyes in solution were nearly identical as there was no change in the D-A-D SQ framework; however, remarkable changes with respect to the power conversion efficiencies (PCE) were observed depending upon the position of alkyl groups in the dye. Introduction of alkyl groups to the indoline unit that was away from anchoring unit were helped in more dye loading with controlled organization of dyes on surface, increased charge transfer resistance, long electron lifetime, and hence higher PCE than that of the corresponding isomer in which the alkyl groups funtionalized indoline unit contains the carboxylic acid anchoring group. Careful analysis of incident photon-to current conversion efficiency (IPCE) profiles indicated the presence of aggregated structure on the TiO2 surface that contributes to the charge injection in the presence of a coadsorbent. A dye-sensitized solar cell (DSSC) device made out of SQ5 was achieved an efficiency of 9.0%, with an open-circuit potential (V-oc) of 660 mV and short-circuit current density (J(sc)) of 19.82 mA/cm 2, under simulated AM 1.5G illumination (100 mW/cm(2)). The IPCE profile of SQ5 shows an onset near to 750 nm with a good quantum efficiency (>80%) in the range of 550-700 nm, indicating the importance of self-organization of dyes on the TiO2 surface for an efficient charge injection. This present investigation revealed the importance of position of alkyl groups in the squaraine-based dyes for the better PCE.

Heterotriangulene-based unsymmetrical squaraine dyes: synergistic effects of donor moieties and out-of-plane branched alkyl chains on dye cell performance - Karjule, Neeta; Munavvar, Fairoos M. K.; Nithyanandhan, Jayaraj (Journal of Materials Chemistry A, 2016)
Unsymmetrical squaraine sensitizers with two different donor moieties, triphenylamine (NSQR) and heterotriangulene (NSQ1–3), for dye-sensitized solar cells (DSSCs) have been designed and synthesized. These dyes utilize the indolium moiety to control charge recombination dynamics at the TiO2-dye-electrolyte interface by connecting linear and branched alkyl functionalities. In the present study, an efficient heterotriangulene (HT) donor and a branched alkyl group at sp3-C atoms were strategically incorporated to increase the power conversion efficiency (PCE) of zwitterionic dyes by improving photo-current density (Jsc) and open-circuit potential (Voc) of the cell. Among these four dyes, NSQ3 exhibited the highest efficiency of 6.73% with a Jsc of 18.74 mA cm−2, Voc of 0.53 V, and fill factor (ff) of 68.3%, without any co-adsorbent under an irradiance of 100 mW cm−2 (simulated AM 1.5G sunlight). In the presence of 3α,7α-dihydroxy-5β-cholanic acid (CDCA), NSQ1, NSQ2 and NSQ3 showed an efficiency of 7.07%, 7.38% and 7.17%, respectively. Despite the low Voc, far red light harvesting efficiency, reduced dye aggregation, long lifetime (τ) of injected electrons and high quantum efficiency of NSQ1–3 played constructive roles in achieving high PCE efficiency. Deceleration of charge recombination for NSQ dye cells was further studied by electrochemical impedance spectroscopy (EIS) and open-circuit photo-voltage decay (OCVD) measurements.

Interplay between pi-bridges and positions of branched alkyl groups of unsymmetrical D-A-D-pi-A squaraines in dye-sensitized solar cells: mode of dye anchoring and the charge transfer process at the TiO2/Dye/electrolyte interface - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Far-red-absorbing squaraines possessing high molar absorptivity (>10(5) M-1 cm(-1)) are being attracted as high-efficiency chromophores in dye-sensitized solar cells (DSSCs). A series of donor acceptor -donor-pi spacer-acceptor (D-A-D-pi-A) unsymmetrical squaraines, PSQ1-5, with indoline donor and squaric/cyanoacetic acid acceptor units, were designed for sensitized solar cells. For extending the absorption toward the near-infrared region (NIR) and controlling the orientation on the TiO2 surface, benzene (PSQ1 and PSQ2) and thiophene (PSQ3-5) 7r-spacers and out-of-plane branched alkyl groups at the indoline that are away (PSQ1, PSQ3, and PSQS) or near (PSQ2 and PSQ4) the anchoring group, respectively, were introduced. Dynamic aggregation tendency of PSQ1 and PSQ3 than that of their isomers systematically modulates the orientation on the TiO2 surface, which in turn enhances photovoltaic performance. Absorptance on a thin transparent TiO2 film shows a visible-to-NIR response with an onset around 800 nm for PSQ3-5. Although there is resemblance in electrochemical redox levels, their high injection efficiency and recombination resistance differentiated impact on the way of anchoring and the dihedral angle between D-A-D units and g-spacers. DSSCs sensitized with PSQS achieved a PCE of 8.15% under simulated AM 1.5G illumination (100 mW cm(-2)), with the current density (j) and open-circuit voltage (Voc) of 19.73 mA cm(-2) and 630 mV, respectively. A clear comparison of the incident-photon-to-current conversion efficiency versus the light-harvesting efficiency correlates the structure-property relationship with J obtained for PSQ dyes. Electrochemical impedance spectroscopy was carried out to examine the TiO2/dye/electrolyte interface for further confirmation of the enhanced PCE of top-se-alkylated PSQS over that of other dyes.
Keywords: D-A-D-pi-A framework; dye-sensitized solar cell; H- and J-type aggregation; orientation of dyes; static/dynamic aggregates; unsymmetrical squaraine

Molecular control of the band edge movement and the recombination process in donor-acceptor hemicyanine-sensitized solar cells - Karjule, Neeta; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2017)
The presence of downward shift in the band edge and the recombination reactions in the hemicyanine-sensitized solar cell reduces the open-circuit potential (V-oc) and the short-circuit current density (J(sc), which in turn decreases the dye cell performance. Choosing either an electrolyte possessing minimum overpotentials or a systematic dye design which can efficiently suppress the diffusion of charged species toward the TiO2 can improve the overall power conversion efficiency (PCE). Here, a series of donor acceptor (D-A) hemicyanine dyes were synthesized utilizing a planar heterotriangulene (HT) or triphenylamine (TPA) donor and alkyl-functionalized indolium carboxylic acid acceptor unit. By introducing strong HT donor instead of TPA, the photophysical, and electrochemical properties of D-A dyes are significantly modulated. The strong donor nature of HT and effective passivation of surface by hydrophobic alkyl chains close to the anchoring group for NC3 dye exhibits an average PCE of 4.34% with a V-oc of 0.416 V, J(sc) of 20.04 mA cm(-2), and fill factor (ff) of 52.03% under simulated AM 1.5G illumination (100 mW cm-2) without 3 alpha,7 alpha-adihydroxy-5 beta-cholic acid coadsorbent (CDCA). The intrinsic dipole of the hemicyanine dye and the presence of Li+ ions in iodide/triiodide redox couple without tert-butylpyridine (TBP) additive induces a downward shift in conduction band edge (E-CB) of TiO2. By rational molecular design, the extend of shift in E-CB is controlled and enhanced the V-oc. Electrochemical impedance spectroscopy (EIS) studies revealed the high charge transfer resistance (R-ct) and long lifetime (tau) of injected electrons in HT-based dyes than that of TPA derivatives, which provide insight into the passivation of Li+ and I- ions by current D-A dye design possessing alkyl functionalities to increase both the J(sc) and V-oc.

Orthogonally functionalized donor/acceptor homo- and heterodimeric dyes for dye-sensitized solar cells: an approach to introduce panchromaticity and control the charge recombination - Sil, Manik Chandra; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Punitharasu, Vellimalai; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Organic dyes possessing conjugated pi-framework forms closely packed monolayers on photoanode in dye-sensitized solar cell (DSSC), because of the limitation to control the orientation and the extend of intermolecular pi-pi interaction, self-aggregation of dyes leads to reduced cell performance. In this report, a series of homodimeric (D-1-D-1, and D-2,-D-2) and heterodimeric (D-1-D-2 and D-2-D-4) donor/acceptor (D/A) dyes containing spiroBiProDOT pi-spacer were designed and synthesized by utilizing Pd-catalyzed direct arylation reaction and correlates the device performance with monomeric dyes (D-1 and D-2). Both the thiophenes (pi-spacer) of spiroBiProDOT were functionalized with same or different donor groups which led to homodimeric and heterodimeric chromophores in a single sensitizer. The homodimeric spirodye D-1-D-1 showed higher power conversion efficiency (PCE), of 7.6% with a V-oc and J(sc) of 0.672 V and 16.16 mA/cm(2), respectively. On the other hand, the monomeric D-1 exhibited a PCE of 3.2% (V-oc of 0.64 V and J(sc) of 7.2 mA/cm(2)); which is lower by 2.4 fold compared to dimeric analogue. The spiro-unit 20 provides flexibility between the incorporated chromophores to orient on TiO2 due to four sp(3)-centers, which arrest the molecular motions after chemisorption. This study shows a new molecular approach to incorporate two chromophores in the dimeric dye possessing complementary absorption characteristics toward panchromatic absorption. The attenuated charge recombination at TiO2/Dye/redox couple interface in case of D-1-D-1, owing to better passivation of TiO2 surface, was elucidated through impedance analysis. The FT-IR spectrum of D,-D, adsorbed on TiO2 film indicated both the carboxylic units were involved in chemisorption which makes strong coupling between dye and TiO2.

Panchromatic sensitizer for dye-sensitized solar cells: un-symmetrical squaraine dyes incorporating benzodithiophene π-spacer with alkyl chains to extend conjugation, control the dye assembly on TiO2 and retard charge recombination - Bisht, Rajesh; Munavvar, Fairoos Mk; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (Journal of Organic Chemistry, 2017)
Metal-free near-infrared (NIR) active unsymmetrical squaraine dyes, RSQ1 and RSQ2, with benzodithiophene (BDT) π-spacer and cyanoacrylic acid acceptor were synthesized by utilizing palladium catalyzed direct (hetero)arylation reaction. Methyl and 2-ethylhexyl groups were strategically placed at the BDT unit for RSQ1 and RSQ2 respectively, to investigate the effect of alkylated π-spacer on dye aggregation on the TiO2 surface and recombination reactions at TiO2/dye/electrolyte interface. These dyes have strong absorption ( ε>10(5) M(-1)cm(-1)) in near-infra red (NIR) region and exhibit similar optical and electrochemical properties as they have same conjugated framework. RSQ2 performed better than RSQ1 owing to its higher open-circuit voltage (Voc) and fill factor (ff) in spite of having comparable short-circuit current density (Jsc). The panchromatic incident photon-to-current conversion efficiency (IPCE) response was also observed for both the dyes. RSQ2 showed power conversion efficiency (PCE) of 6.72% with short-circuit current density (Jsc) of 18.53 mA/cm(2), open circuit voltage (Voc) of 0.538 V, and fill factor (ff) of 67.4%, without any co-adsorbent. Attenuation of the charge recombination for RSQ2 was revealed by electrochemical impedance analysis (EIS) and open-circuit potential decay transients (OCVD), which attributes to its higher Voc and ff in comparison to RSQ1.

Fused fluorenylindolenine-donor-based unsymmetrical squaraine dyes for dye-sensitized solar cells - Bisht, Rajesh; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Karjule, Neeta; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
A series of four unsymmetrical squaraine dyes, XSQ1-4, were synthesized using a fused fluorenylindolenine-based donor unit for dye-sensitized solar cells (DSSCs). The fused structure of fluorenylindolenine helped in moving the absorption toward the near-infrared (NIR) region, and the two sp(3)-C centers available on this donor were utilized to incorporate out-of-plane alkyl chains in opposite directions to control the dye-dye interactions on the TiO2 surface. High extinction coefficient (epsilon >= 10(5) M-1 cm(-1)) for absorbing NIR photons and suitable highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels with respect to the conduction band of TiO2 and electrolyte for charge injection and dye regeneration processes, respectively, make these dyes potential sensitizers for DSSCs. Introduction of branched alkyl groups in the pi-framework helped in controlling dye aggregation to reduce exciton quenching and assisted in TiO2 surface passivation to avoid the charge recombination process. Furthermore, having a naphthyl group on the indole part of the anchoring group containing segment helped to red-shift the absorption spectrum of dyes 15 nm toward the NIR region (XSQ3-4). Among all of the dyes under investigation, XSQ2 gave the best photovoltaic performance, having a short-circuit current density (J(SC)) of 13.99 mA cm(-2), open -circuit voltage (V-OC) of 0.66 V, and a fill factor (ff) of 0.71, with a device performance (eta) of 6.57%. Electrochemical impedance spectroscopy revealed higher electron lifetime on TiO2 for XSQ2, which helps to avoid the charge recombination process.
Keywords: Dye-sensitized solar cells; fluorenylindolenine; H- and J-type aggregation; NIR absorption; out-of-plane alkyl groups; squaraine dyes

Homo- and heterodimeric dyes for dye-sensitized solar cells: panchromatic light absorption and modulated open circuit potential - Sil, Manik Chandra; Sudhakar, Vediappan; Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ChemPlusChem, 2018)
The design of dyes for panchromatic light absorption has attracted much attention in the field of dye-sensitized solar cells (DSSCs). An approach to enhance panchromatic light absorption utilizes mixtures of complementary light-absorbing dyes as well as dyes with specific anchoring groups that facilitate interfacial charge transfer with TiO2. Dipole-dipole interactions between the dye molecules on the surface broaden the spectrum, which results in decreased DSSC device performance. However, controlled aggregation of dyes results in broadening the spectral profile along with enhanced photocurrent generation. To control the dye-dye interaction, dimeric dyes with different dipole lengths D-1-D-sq, D-sq-D(sq)were systematically designed and synthesized. The photophysical and electrochemical properties were evaluated and the E-HOMO and E-LUMO levels were determined; these energy levels determines the electron injection from E-LUMO of the dye to E-CB of TiO2 and regeneration of oxidized dye by the electrolyte, respectively. The absorption spectra of D-sq-D-sq, D-1-D-sq were broadened in solution compared to model dye D-sq; this indicates that the dye-dye interaction is prominent in solution. In D-1-D-sq excitation energy transfer between photoexcited D-1 and D-sq was explained by using Forster resonance energy transfer (FRET). The homodimeric dye showed a device performace of 2.8 % (V-oc 0.607, J(sc) 6.62 mA/cm(2), ff 69.3 %),whereas the heterodimeric dye D-1-D-sq showed a device performance of 3.9 % (V-oc 0.652 V, J(sc) 8.89 mA/cm(2), ff 68.8 %). The increased photocurrent for D-1-D(sq)is due to the panchromatic IPCE response compared to D-sq-D-sq. The increased V(oc)is due to the effective passivation of the TiO2 surface by the spirolinker, and the effective dipole moment that shifts the conduction band on TiO2. Hence, the open circuit potential, V-oc, for the devices prepared from D-sq, D-1-D-sq and D-sq-D(sq)were systematically modulated by controlling the intermolecular pi-pi and intramolecular dipole-dipole interactions of the dimeric dyes.

Indenoquinaldine-based unsymmetrical squaraine dyes for near-infrared absorption: investigating the steric and electronic effects in dye-sensitized solar cells - Bisht, Rajesh; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Chemistry-A European Journal, 2018)
A series of near-infrared (NIR)-responsive unsymmetrical squaraine dyes (ISQ1-3) incorporating a fused indenoquinaldine-based donor have been designed and synthesized. C-12 alkyl chains were incorporated at the sp(3)-hybridized carbon center of the indene unit of the indenoquinaldine in an out-of-plane orientation to control dye aggregation on the surface of titanium dioxide, and indole (ISQ1), benzo[e]indole (ISQ2), and quinoline (ISQ3) moieties were included as the donor component bearing the anchoring carboxy group to extend the absorption in the NIR region and to systematically study the effect of the electronic modification on the performance of dye-sensitized solar cells (DSSC). All the dyes exhibit intense absorption (epsilon >= 10(5) m(-1) cm(-1)) in the NIR region, and the dye-adsorbed TiO2 films exhibit broad panchromatic absorption. The incident photon-to-current efficiency (IPCE) spectrum of the ISQ3-based DSSC device displays a panchromatic IPCE response up to 880 nm. Additionally, the ISQ3-sensitized device provides the best efficiency of 4.15% with a short circuit current density (J(SC)) of 10.02 mA cm(-2), open-circuit voltage (V-OC) of 0.58V, and fill factor (ff) of 72% in the presence of 10 equivalents of 3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid (CDCA). Electrochemical impedance spectroscopy analysis showed attenuated charge recombination in the ISQ3-sensitized DSSC, which contributes to its higher value of V-OC compared with the other dyes.

Modulated photochemical reactivities of O-acetylated (3', 5'-dimethoxyphenyl) heteroaryl acyloin derivatives under direct irradiation and photo-induced electron transfer conditions - Bisht, Rajesh; Singh, Saumya; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemical & Photobiological Sciences, 2018)
3', 5'-Dimethoxybenzoin esters are important photoremovable protecting groups which form 2-phenylbenzofuran derivatives upon photo-release. We utilized a similar concept to test a photochemical method of installing a benzofuran moiety to the conjugated backbone by subjecting O-acetylated (3', 5'-dimethylphenyl) heteroaryl acyloin derivatives through direct photo irradiation and a photo-induced electron transfer reaction. These photochemical methods were explored for a variety of heteroaromatic substrates appended on the ketone part of the O-acetylated cross-acyloin derivatives. The furan, thiophene and bithiophene derivatives led to the expected cyclized (benzofuran capped) products but the derivatives with extended conjugation decomposed under direct irradiation. However, under irradiation in the presence of an electron donor such as triethylamine, the extended acyloin derivatives afforded both cyclized and deacetoxylated products. The semiconducting nature of the extended cyclized products was also explored and tested for solution-processed organic field effect transistors, providing a maximum hole mobility of 1.3 x 10(-6) cm(2) V-1 s(-1).

Modulation of reactivity of singlet radical pair in continuous flow: photo-fries rearrangement - Karjule, Neeta; Sharma, Mrityunjay K.; Nithyanandhan, Jayaraj; Kulkarni, Amol (Journal of Photochemistry and Photobiology A: Chemistry, 2018)
Photo-Fries rearrangement of phenyl benzoate is studied using continuous flow for modulating the reactivity of singlet radical pair by changing the viscosity of the solvent. The effect of flow and proximity of the reactants with the light source on the reactivity of radical pair, formed from singlet excited state was investigated in details. In non-viscous solvent, the results from flow synthesis were comparable to batch reactor. In viscous solvents, selectivity of ortho- and para-isomers (o-/p- isomer) of the product could be controlled by changing viscosity as well as the flow rate. Using flow synthesis, ortho- and para-isomer ratio was obtained as high as 8.45 which are twice as compared to batch experiment with in fraction of residence time.

Self-assembly of Cis-configured squaraine dyes at the TiO2-dye interface: far-red active dyes for dye-sensitized solar cells - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
To synergize both steric and electronic factors in designing the dyes for dye-sensitized solar cells, a series of cis-configured unsymmetrical squaraine dyes P11-P15 with suitably functionalized alkyl groups and squaric acid units containing the electron-withdrawing groups were synthesized, respectively. These dyes capture the importance of (i) the effect and position of branched alkyl groups, (ii) mono- and di-anchoring groups containing dyes, and (iii) further appending the alkyl groups through the cyanoester vinyl unit on the central squaric acid units of DAD-based cis-configured squaraine dyes. All the above factors govern the controlled self-assembly of the dyes on the TiO2 surface which helps to broaden the absorption profile of the dyes with an increased energy-harvesting process. With respect to the position of the branched alkyl groups, dye P11 with the sp(3)-C and N-alkyl groups away from the TiO2 surface showed a better device efficiency of 5.98% (J(sc) of 14.46 mA cm(-2), V-oc of 0.576 V, and ff of 71.8%) than its positional isomer P12 with 3.45% (J(sc) of 8.78 mA cm(-2), V-oc of 0.554 V, and ff of 70.9%). However, with respect to the dyes containing mono- and di-anchoring groups, P13 with two anchoring units exhibited a superior device performance of 7.58% (J(sc) of 17.12 mA cm(-2), V-oc of 0.618 V, and ff of 71.7%) in the presence of optically transparent co-adsorbent CDCA (3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid) than dyes P11 and P12.

Effect and position of spiro-bipropylenedioxythiophene pi-spacer in donor-pi-spacer-acceptor dyes for dye-sensitized solar cell - Sil, Manik Chandra; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Dyes and Pigments, 2019)
Improper orientation and self-assembly of dyes on TiO2 surface are the main disadvantages at the dye-TiO2 interface that governs both charge injection and dye regeneration processes. In this report, a series of homo spiro-dimeric donor-pi-spacer-acceptor (D-pi-A) dyes based on bithiophene and terthiophene spacers with two-anchoring group containing dyes, TT1, T1T, TT1T were designed and synthesized by Pd-catalyzed successive Suzuki coupling followed by direct arylation reactions. The position of branching centre in TT1 and T1T was systematically varied, where the spiro unit was placed near and away from the anchoring carboxylic acid unit, respectively. The dimeric spiro-dye T1T showed device performance, which is 1.6 fold higher than its structural isomeric analogue TT1, of 3.9% with a V-oc and J(sc) of 0.593 V and 9.09 mA/cm2, respectively, whereas for the isomeric analogue TT1 a device performance of 2.45% (V-oc of 0.568 V and J(sc) of 6.25 mA/cm2) under simulated 1 Sun (100 mW/cm2) condition. The improved Voc for the dye T1T compared to TT1 dye was ascribed to the dipole moment exerted by the dyes on TiO2 surface. Further the PCE of 4.16% (V-oc 0.589 V, J(sc) 9.79 mA/cm2 respectively) maximum was observed, when an extra thiophene unit was inserted in between the donor and pi-spacer in dye TT1T. The shifting the position of branching spiroBiProDOT pi-spacer makes an impact on the device performance by synergistically enhancing both Voc and Jsc.
Keywords: CDCA; D-pi-A Spiro dye; Dye aggregation; dye-sensitized solar cell; spiroBiProDOT spacer

pi-Extended cis-configured unsynimetrical squaraine dyes for dye-sensitized solar cells: panchromatic response - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2019)
{Light absorbing sensitizer is the heart of the third generation photovoltaic technologies such as dye sensitized solar cells. Despite possessing large extinction coefficients for the metal-free organic dyes, the light harvesting efficiency is limited with the narrow absorption 20 profile in either visible or NIR regions of the solar spectrum. Though monolayer formation of organic sensitizers on semiconducting metal oxide surface leads to dye-dye interaction that leads to broadening the absorption profile, the contribution of the aggregated state to the power conversion process is found out to be poor. Here, we have engineered far-red active pi-extended cis-configured unsymmetrical squaraine dyes with carboxylic acid and cycnoacetic acid as anchoring groups with controlled aggregation and panchromatic light absorption by including the steric and electronic factors. The presence of sp(3)-C (out-of-plane) and N-alkyl (in-plane) groups played an important role in modulating the assembly of the dyes on the TiO2 electrode; the cis-squaraine unit helps to extend the conjugation in the NIR region besides enhancing the visible transition and the incident photon-to-current conversion efficiency profile that showed the importance of anchoring groups for the panchromatic response. Dye PSQ10 showed solar-to electric conversion with an onset of 850 nm with the device performance of 7.0% (V-oc = 0.581 V, J(sc) = 17.06 mA/cm(2)
Keywords: cis-squaraine dyes; Dye aggregation; Dye-sensitized solar cells; extended far-red absorption; panchromatic response

Alkyl-group-wrapped unsymmetrical squaraine dyes for dye-sensitized solar cells: branched alkyl chains modulate the aggregation of dyes and charge recombination processes - Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2020)
Electron transfer processes at the interfaces dictate the factors that improve the photovoltaic parameters, such as open-circuit voltage (V-oc) and short-circuit current (J(sc)), of a dye-sensitized solar cell device, besides selection of a set of suitable anode, dye, electrolyte, and cathode materials. An inefficient charge injection process at the dye-TiO2 interface and charge recombination at the TiO2-dye/electrolyte interface have detrimental effects on improving both J(sc) and V-oc. Hence, tailoring the factors that govern the improvement of J(sc) and V-oc will be an ideal approach to get the desired sensitizers with good device efficiencies. Squaraines are far-red-active zwitterionic dyes and have a high molar extinction coefficient along with unique aggregation properties due to the large dipole moment associated with them. Here, we report a series of unsymmetrical squaraine dyes, SQS1 to SQS6, with systematic variation of alkyl groups at the sp(3)-C and N-atoms of the indoline unit that is away from the anchoring group to control the dye-dye interactions on the TiO2 surface. The branched alkyl groups help in modulating the self-assembly of sensitizers on the TiO2 surface, besides passivating the surface that helps avoid the charge recombination processes. Light harvesting efficiency and cyclic voltammetry studies of dye-sensitized TiO2 electrodes indicate that the aggregation and charge hopping process between the dye molecules can be modulated, respectively, by systematically increasing the number of carbon atoms in the alkyl groups. Such a variation in the branched alkyl group helps enhance V-oc from 672 (SQS1) to 718 mV (SQS6) and J(sc) from 7.95 (SQS1) to 12.22 mA/cm(2) (SQS6), with the device efficiency ranging from 3.82% to 6.23% without any coadsorbent. Dye SQS4 achieves the highest efficiency of 7.1% (V-oc = 715 mV, J(sc) = 13.05 mA/cm(2)) with coadsorbent chenodeoxycholic acid (CDCA) using an iodine (I-/I-3(-)) electrolyte compared to its analogues. An analysis of the incident photon-to-current efficiency profiles indicates that the major contribution to photocurrent generation is from the aggregated squaraine dyes on TiO2.
Keywords: aggregation of dye; charge injection; charge recombination; Dye-sensitized solar cells; unsymmetrical squaraines

Unsymmetrical squaraine dyes for dye-sensitized solar cells: position of the anchoring group controls the orientation and self-assembly of sensitizers on the TiO2 surface and modulates its flat band potential - Singh, Ambarish Kumar; Maibam, Ashakiran; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Kudlu, Ashwath; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2020)
The position of the anchoring group is systematically changed with a series of alkyl group wrapped donor-acceptor-donor (D-A-D) based squaraine dyes, 4-SQ to 7-SQ, for the use in dye-sensitized solar cells (DSSCs). By this approach, the orientation as well as the self-assembly of the sensitizers can be controlled on the semiconducting TiO2 surface. All of the dyes functionalized with hydrophobic alkyl groups at sp(3)-C and N atoms of the indoline units that is far away from the TiO2 surface to control the self-assembly of dyes and passivate the surface. Controlling both the orientation as well as the self-assembly of the sensitizers synergistically enhances the V-oc of the DSSC device by imparting the dipole moment on the TiO2 surface and minimizing the interfacial charge recombination process of electrons from TiO2 to the oxidized electrolyte, respectively. Further, the presence of a meta-carboxyl group with respect to the N atom of the indoline donor unit for the dyes 4-SQ and 6-SQ makes them nonconductive for the charge injection process, which sheds light on the importance of through-space electron transfer for the device performance. Emission from the relaxed twisted state was found to be a deactivation pathway for 4-SQ on TiO2 and ZrO2, which revealed the importance of structural factors that promote spatial interaction between the sensitizer and metal oxide surface. Computational studies showed the systematic changes in the dipole moment for the sensitizers 4-SQ, 5-SQ, and 6-SQ upon anchoring to the TiO2 surface. The DSSC device performance varied with the position of anchoring groups in the sensitizers. The DSSC device performance of 5-SQ indicates a J(sc) value of 11.35 mA cm(-2), V-oc of 0.698 V, and ff of 77% corresponding to a power conversion efficiency of 6.08% in the presence of 3 equiv of coadsorbent CDCA, which is nearly 1.5 times higher than 6-SQ (V-oc 0.7 V, J(sc) 7.76 mA cm(-2), ff 76%, and eta 4.14%) and 2.6 times higher than 4-SQ (V-oc 0.658 V, J(sc) 4.42 mA cm(-2), ff 78%, and eta 2.28%). IPCE studies revealed the importance of orientation for the charge injection and self-assembly of dyes, as devices with 5-SQ and 6-SQ as a sensitizer showed 94 and 77% response at 578 nm, respectively, which correspond to the aggregated structure of the dye. Mott-Schottky and IPCE experiments showed that the orientation of sensitizers could modulate the V-oc due to the shift in the flat band potential of TiO2.

Amphiphilic indoline-based unsymmetrical squaraine dyes for dye-sensitized solar cells: modulating the dye-TiO2/electrolyte interface for nonaqueous and aqueous electrolytes - Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2021)
A high molar extinction coefficient with sharp absorption properties from the range of visible to near-infrared regions makes squaraine dyes very attractive and potential chromophores for dye-sensitized solar cell (DSSC) applications. Here, we report a series of alkyl groups and glycolic chain [triethylene glycol (TEG)]-wrapped amphiphilic indoline-based unsymmetrical squaraine dyes, where the number of carbon atoms in the alkyl groups and TEG was systematically changed by incorporating the alkyl groups and TEG within the dye molecule for controlling the self-assembly of the dyes on the TiO2 surface and to improve the interfacial properties at the dye-TiO2/electrolyte interface. Due to the same skeletal characteristics, ASQ dyes showed similar photophysical and electrochemical properties in solution. Photovoltaic characterization of ASQ dyes was carried out in nonaqueous and aqueous electrolytes to evaluate the effect of alkyl groups and TEG on nonaqueous and aqueous DSSC device performances. VOC, JSC, and photovoltaic efficiencies were systematically enhanced by increasing the number of carbon atoms of alkyl groups into the dye molecules for nonaqueous DSSCs. Furthermore, addition of chenodeoxycholic acid (CDCA) decreased the charge recombination processes and resulted in enhanced efficiency, VOC, and JSC (enhanced incident photon-to-current conversion efficiency performance) compared to that without CDCA. The ASQ4 dye gave the highest nonaqueous DSSC efficiency of 6.39%, a VOC of 711 mV, and a JSC of 12.18 mA/cm2 with 2 equiv of CDCA in the ASQ dye series. Furthermore, increased carbon atoms in the alkyl groups showed a detrimental effect on the aqueous DSSC efficiency due to the mismatch in the polarity at the dye-TiO2/electrolyte interface, being the reason for the decreased device efficiencies from ASQ2 to ASQ4 dyes. The ASQ2 dye gave the highest aqueous DSSC efficiency of 2.36%, a VOC of 611 mV, and a JSC of 4.75 mA/cm2 without CDCA in the ASQ dye series.

D-A-D based complementary unsymmetrical squaraine dyes for co-sensitized solar cells: enhanced photocurrent generation and suppressed charge recombination processes by controlled aggregation - Singh, Ambarish Kumar; Veetil, Athulya Nellur; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2021)
A series of donor-acceptor-donor (D-A-D) based unsymmetrical squaraine dyes have been synthesized with indoline and aniline as donor units. The sp(3)-C, N atoms of the indoline and N atom of the aniline donors are appended with alkyl groups systematically to control the self-assembly of dyes on TiO2 and to passivate the photoanode that helps in improving the open circuit voltage (V-oc) of the dye-sensitized solar cell (DSSC) device. The resulting dyes, AK1-4, possess strong absorptions between 529 and 541 nm with extinction coefficients of 1.44-1.84 X 10(5) M-1 cm(-1). Photophysical and electrochemical studies revealed that the lowest unoccupied molecular orbital and highest occupied molecular orbital of the dyes are aligned with the conduction band of TiO2 and the redox function of the electrolyte for the efficient charge injection and dye regeneration processes, respectively. A DSSC device performance for AK4 of 7.93% (V-oc of 815.88 mV and short circuit current density (J(sc)) of 12.4 mA/cm(2)) is obtained, with an incident photon to current conversion efficiency (IPCE) response of 92% at 473 nm and 86% at 566 nm without sensitizing with coadsorbent. IPCE studies revealed the equal contribution for the photocurrent generation from the H-aggregated structures. Further, such a high V-oc and DSSC efficiency have been observed first time for this class of zwitterionic dyes with the I-/I-3(-) electrolyte without sensitizing with coadsorbent. The importance of introducing the alkyl groups at the indoline as well as aniline donor units for the synergistic boosting of both V-oc, and J(sc) is compared with the model dye AK1. Complementary light absorbing dyes SQ1 and SQS4 possess absorption at 643 nm with extinction coefficients of 1.4 and 3.0 x 10(5) M-1 cm(-1), respectively. A cosensitized device performance of 9.36% is obtained for the AK4:SQS4 (1:1) combination in the I-/I-3(-) electrolyte. The IPCE profile indicates a good response over 450-700 nm with 94% at 621 nm. The importance of aggregated structures from both the dyes AK4 and SQS4 for photocurrent generation is realized.
Keywords: aggregation of dyes; co-sensitization; extension of conjugation; H-aggregate; squaraine dyes

Indoline-based donor-pi-acceptor visible-light responsive organic dyes for dye-sensitized solar cells: co-sensitization with squaraine dye for panchromatic IPCE response - Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2022)
A series of metal-free indoline-based donor-pi-acceptor (D-pi-A) visible-light active organic dyes, where an indoline unit wrapped with alkyl or alkyl and glycolic (TEG) groups is used as a donor, a mono- or bi-thiophene unit is used as a pi-spacer, and cyanoacrylic acid acts as an acceptor unit, have been designed and synthesized for dye-sensitized solar cell (DSSC) application. These dyes showed three absorption bands in a dichloromethane solution: the first and second transitions are observed in the UV (337-385 nm) and visible (477-514 nm) regions and correspond to pi-pi* and intramolecular charge transfer (ICT) transition, respectively, whereas the third absorption band obtained in the near-IR (629-758 nm) region has been observed for the first time for a D-pi-A type dye architecture. Furthermore, the ICT transition band for AKT dyes showed negative solvatochromism with increasing polarity of solvents. Photovoltaic characterizations for AKT dyes have been systematically studied with a cobalt electrolyte to evaluate the effect of thiophene incorporation and alkyl group substitution by the TEG group on the DSSC device performance. Here, AKT2 showed the highest DSSC efficiency of 3.16% with V-OC of 0.680 V and J(SC) of 6.24 mA/cm(2) without chenodeoxycholic acid (CDCA) in the AKT dye series, whereas DSSC efficiencies for AKT dyes were not affected much upon further addition of CDCA. Furthermore, AKT dyes were co-sensitized with a complementary optical responsive indoline-based SQS4 dye and showed enhanced efficiency. The combination of AKT2/SQS4 dyes with a ratio of 1:1 showed a maximum of 5.20% co-sensitized solar cell efficiency compared to other dye combinations with the cobalt electrolyte.
Keywords: Dye-sensitized solar cells; indoline-based donor-pi-acceptor dye; intramolecular charge transfer; metal-free organic dye; panchromatic-light absorption; Solvatochromism

D-A-D-based unsymmetrical thiosquaraine dye for the dye-sensitized solar cells(dagger) - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemistry and Photobiology, 2023)
In dye-sensitized solar cell, modulating the electronic properties of the sensitizer by varying the donor, pi-spacer, acceptor and anchoring groups help optimizing the structure of the dye for better device performance. Here, a donor-acceptor-donor-based unsymmetrical thiosquaraine sensitizer (SQ5S) has been designed and synthesized. Photophysical, electrochemical, theoretical and photovoltaic characterizations of SQ5S dye have been compared with its oxygen analog, SQ5. The incorporation of the sulfur atom in the acceptor unit of SQ5S dye showed an intense peak at 688 nm, which was 38 nm of red-shifted and showed the panchromatic light harvesting response with the onset of 850 nm compared with SQ5 dye. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of electrolyte for the charge injection and the dye-regeneration processes, respectively. Photovoltaic efficiency of 1.51% (V-OC 610 mV, J(SC) 3.07 mA cm(-2), ff 81%) has been achieved for SQ5S dye, whereas SQ5 showed the device performance of 5.43% (V-OC 723 mV, J(SC) 9.3 mA cm(-2), ff 80%). The decreased device performance for the dye SQ5S has been attributed to the favorable intersystem crossing process associated with the photoexcited SQ5S that reduces the driving force for the charge injection process.

Modular TiO2-squaraine dyes/electrolyte interface for dye-sensitized solar cells with cobalt electrolyte - Singh, Ambarish Kumar; Sudhakar, Vediappan; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2023)
Strategies to diminish both charge recombination and aggregation of dyes on the photoanode by functionalizing the sensitizer with alkyl groups is the best approach to achieve high dyesensitized solar cell (DSSC) efficiency. Development of such a photoanode with NIR-active dyes which is compatible with a cobalt electrolyte is important to enhance the photovoltaic performance. In this report, alkyl-group-wrapped donor-acceptor-donor (D-A-D) based unsymmetrical squaraine dyes have been used for DSSC device characterization with a cobalt electrolyte. Surface passivation of photoanode was varied systematically by the extent of functionalization with alkyl groups to avoid charge recombination. DSSC device performance of 5.92% was achieved for an alkyl-group-wrapped squaraine dye with a cobalt electrolyte. Hence, appending the alkyl groups on the donor unit of squaraine dyes helps passivating the photoanode, whereas introducing hydrophilic groups provides a leaky surface where oxidized electrolyte species reach the titanium-metal-oxide surface which promotes the charge recombination process.
Keywords: counter-electrode; DSSC device efficiency; Dye-sensitized solar cells; Electrolytes; unsymmetrical squaraine dye

Steric and electronic effect in unsymmetrical squaraine dyes for dye-sensitized solar cells - Nawghare, Indrajeet S.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of physical chemistry C, 2023)
Functionalizing the light harvesting sensitizers with additional electron-donating or -withdrawing groups is a potential approach to modulate the photophysical and electrochemical properties which in-turn optimizes the driving force associated with the charge injection and dye-regeneration processes at the dye-TiO2/electrolyte interface and the photovoltaic device performance in dye-sensitized solar cells (DSSCs). Furthermore, modulated electronic levels of the dyes provide an opportunity to reduce the overpotential associated with the dye-regeneration process and make the dye-TiO2 interface compatible with various electrolytes. Furthermore, an in-built steric feature by means of introducing linear/branched alkyl groups in the sensitizer is important in controlling the aggregation of dyes on the TiO2 surface. Hence, to integrate both steric and electronic properties, a series of alkyl group-wrapped unsymmetrical squaraine dyes (SQ-X) with electron-donating and -withdrawing groups have been designed, synthesized, and utilized for DSSC device fabrication. These dyes are functionalized with alkyl groups at both sp(3)-C and N-atoms of the indoline donor moiety at the nonanchoring side to have a similar steric feature. Photophysical and electrochemical studies revealed that the HOMO and LUMO energy levels of the SQ-X series of dyes have been modulated systematically with sufficient driving forces for both charge injection and dye-regeneration processes with iodolyte (I-/I-3(-)) electrolyte. In the presence of electron-donating groups in SQ-X (where X = -NPh2 and -OMe), the HOMO energy levels are less positive than SQ-H, whereas the presence of electron-withdrawing groups such as -CO2Me, -CN, and -NO2 pushed the HOMO energy levels toward more positive potentials. Enhanced photovoltaic performances have been obtained for the dyes containing electron-donating groups, where the dye with the -NPh2 group showed a maximum of eta 7.03% (V-OC 708 mV, J(SC) 13.16 mA cm(-2), and ff 78%). The dye with the strong electron-withdrawing group -NO2 showed an efficiency of 1.49% (V-OC = 634 mV, J(SC) = 3.13 mA cm(-2), and ff 75%). As the dyes with the electron-withdrawing group possess deep positive HOMO energy levels, the DSSC device characterization has been investigated with the Cu+/2+ redox shuttle. The reduced device performance of electron-withdrawing-group-containing dyes is due to the unfavored charge distribution in the LUMO compared to the presence of electron-donating-group-containing dyes, and it was supported by the difference in the charge injection efficiency.
Keywords: cobalt; Donor; Dynamics; Organic dyes

Visible-light-active unsymmetrical squaraine dyes with 1 V of open-circuit voltage for dye-sensitized solar cells - Singh, Amrita; Kumar Singh, Ambarish; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ChemPhotoChem, 2023)
A series of alkyl-group-functionalized, aniline- and indoline-donor-based, unsymmetrical visible-light-active squaraine dyes, AM1-3, were designed and synthesized. Dye-sensitized solar cell (DSSC) devices were fabricated with both I-/I-3(-) and [Cu(tmby)(2)](+/2+) electrolytes. DSSC devices sensitized with the AM1 and AM2 dyes showed relatively high-power conversion efficiency of 7.44 % and 7.22 %, respectively with I-/I-3(-) in the absence of chenodeoxycholic acid (CDCA) than those of the AM3 dye (5.41 %). The [Cu(tmby)(2)](+/2+) electrolyte along with poly(3,4-ethylenedioxythiophene) (PEDOT) as cathode material showed excellent open-circuit potentials (V-OC) of 1030, 1025, and 1001 mV with the DSSC efficiency of 8.05 %, 7.96 %, and 5.84 %, respectively, for the AM1, AM2, and AM3 dyes in the absence of CDCA. Here, the AM1 dye exhibited the maximum DSSC efficiency of 8.05 % and V-OC of 1030 mV, which is the highest obtained efficiency and V-OC for the visible-light active zwitterionic unsymmetrical-squaraine dye with copper-based electrolyte.
Keywords: Cu electrolytes; dihedral angle; Dye-sensitized solar cells; open circuit voltage; squaraine dyes

Visible-light-active unsymmetrical squaraine dyes with pyridyl anchoring groups for dye-sensitized solar cells - Deshmukh, Shivdeep Suresh; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Langmuir, 2023)
Visible-light-active alkyl group-wrapped unsymmetrical squaraine dyes SD1-SD3 were synthesized, featuring an indoline donor and pyridine and carboxylic acid anchoring groups. Their photophysical, electrochemical, and photovoltaic characteristics were examined by fabricating a dye-sensitized solar cell (DSSC) device. Both carboxylic acid and pyridine anchoring groups containing squaraine dyes SD3 and SD2 possess similar photophysical and electrochemical characteristics. However, their photovoltaic performances were completely different. The SD3 dye with the carboxylic acid anchoring group displayed a DSSC device efficiency of 7.20% (V-OC 0.81 V; J(SC) 12.29 mA/cm(2)) using iodolyte (I-/I-3(-)) electrolyte, compared to SD1 (V-OC 0.659 V; J(SC) 4.97 mA/cm(2); and eta - 2.34%) and SD2 (V-OC 0.629 V; J(SC) 1.68 mA/cm(2); and eta - 0.84%), which were featured with pyridyl anchoring groups. These results were attributed to dye loading on the Lewis and Br & oslash;nsted acidic sites of TiO2 and the importance of aggregated structures for photocurrent generation. In the incident photon-to-current efficiency (IPCE) analysis, SD1 dye-sensitized devices exhibited photocurrent generation from both monomeric and aggregated dyes on the TiO2 surface. In contrast, SD2 showed photocurrent generation solely from aggregated states. Despite the introduction of long alkyl chains to reduce dye aggregation and charge recombination, the results indicated preferential charge injection from only the aggregated SD2 dye on TiO2. Fluorescence-quenching experiments indicated an efficient charge transfer from the aggregated SD2 dye to TiO2 compared to that of the monomeric dye. Cosensitization, a method to enhance the light-harvesting efficiency and photocurrent generation in DSSCs, was explored by simultaneously cosensitizing pyridyl-based dyes (SD1 and SD2) with a blue-colored carboxylic acid-based squaraine dye SD4. IPCE analysis demonstrated that both SD1 and SD4 contributed to generating a photocurrent of 9.11 mA/cm(2). The sequential cosensitization of SD1 and SD4 with the coadsorbent CDCA showed the highest performance, with a V-OC of 0.663 V, a J(SC) of 11.43 mA/cm(2), and an efficiency (eta) of 5.20%.
Keywords: co-sensitization; Design; Emmision; Fluorescent Dyes; High-Efficiency; Organic Dye; Ring

Aniline and indoline donors based far-red active unsymmetrical squaraine dyes for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2024)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on the metal-oxide surface by appending the alkyl groups around the donor or pi-spacer unit of the dye is a potential approach to enhance DSSC efficiency. Further, rigidification of the dye structures by cyclization modulates the photophysical properties of the sensitizer. Here a series of donor-acceptor-donor (D-A-D) type far-red active unsymmetrical squaraine dyes (SQA) have been designed and synthesized, where N,N-dimethylaniline, methylated- and branched-indoline have been used as donor units. These dyes showed absorption between 629-654 nm (lambda max) with the molar extinction coefficient of 1.49-1.94x105 M-1 cm-1. Systematic enhancements in DSSC device efficiency have been observed due to the cyclization and alkyl-groups incorporation in this set of dyes which were further enhanced with the addition of chenodeoxycholic acid (CDCA). The highest DSSC device efficiency of 4.78 % (Jsc of 8.77 mA/cm2 and Voc of 692 mV) has been achieved for SQA3. The IPCE profile of SQA dyes indicates the contribution of aggregated structures for the photocurrent generation. Further, co-sensitization of SQA3 dye with a complementary visible light active dye AK4 showed the enhanced device efficiency of 6.27 % with panchromatic IPCE response. Dye rigidification, and controlled aggregation of dyes on TiO2 by means of cyclization of donor unit and introducing the alkyl groups in the dye structure synergistically improve the dye-sensitized solar cell (DSSC) device performance. Donor-Acceptor-Donor (D-A-D) based unsymmetrical squaraine dye SQA3 showed the DSSC device performance of 4.78 %.image
Keywords: co-sensitization; dye-sensitized solar cell; effect of alkyl chain; molecular planarity; squaraine dye

Effect of position of donor units and alkyl groups on dye-sensitized solar cell device performance: indoline-aniline donor-based visible light active unsymmetrical squaraine dyes - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Om., 2024)
Indoline (In) and aniline (An) donor-based visible light active unsymmetrical squaraine (SQ) dyes were synthesized for dye-sensitized solar cells (DSSCs), where the position of An and In units was changed with respect to the anchoring group (carboxylic acid) to have In-SQ-An-CO2H and An-SQ-In-CO2H sensitizers, AS1-AS5. Linear or branched alkyl groups were functionalized with the N atom of either In or An units to control the aggregation of the dyes on TiO2. AS1-AS5 exhibit an isomeric pi-framework where the squaric acid unit is placed in the middle, where AS2 and AS5 dyes possess the anchoring group connected with the An donor, and AS1, AS3, and AS4 dyes having the anchoring group connected with the In donor. Hence, the conjugation between the middle squaric acid acceptor unit and the anchoring -CO2H group is short for AS2, AS5, and AK2 and longer for AS1, AS3, and AS4 dyes. AS dyes showed absorption between 501 and 535 nm with extinction coefficients of 1.46-1.61 x 10(5) M-1 cm(-1). Further, the isomeric pi-framework of An-SQ-In-CO2H and In-SQ-An-CO2H exhibited by means of changing the position of In and An units a bathochromic shift in the absorption properties of AS2 and AS5 compared to the AS1, AS3, and AS4 dyes. The DSSC device fabricated with the dyes contains short acceptor-anchoring group distance (AS2 and AS5) showed high photovoltaic performances compared to the dyes having longer distance (AS1, AS3, and AS4) with the iodolyte (I-/I-3(-)) electrolyte. DSSC device efficiencies of 5.49, 6.34, 6.16, and 5.57% have been achieved for AS1, AS2, AS3, and AS4 dyes, respectively; without chenodeoxycholic acid (CDCA), small changes have been observed in the device performance of the AS dyes with CDCA. Significant changes have been noted in the DSSC parameters (open-circuit voltage V-OC, short-circuit current J(SC), fill factor ff, and efficiency eta) for the AS5 dye while sensitized with CDCA and showed highest DSSC efficiency of 8.01% in the AS dye series. This study revealed the potential of shorter SQ acceptor-anchoring group distance over the longer one and the importance of alkyl groups on the overall DSSC device performance for the unsymmetrical squaraine dyes.

Triazatruxene amine donor-based visible-light-responsive unsymmetrical squaraine dyes for dye-sensitized solar cells - Ingole, Kiran Balaso; Deshmukh, Shivdeep Suresh; Verma, Tushar Singh; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Optimized charge-transfer dynamics at the dye-TiO2/electrolyte interface are required for an enhanced dye-sensitized solar cell (DSSC) device performance. Such an optimized interface enhances the charge-injection, dye-regeneration, and diminished charge-recombination processes, synergistically enhancing the device efficiency. In this study, octupolar-structured sensitizers are designed to improve the interaction between the dye and the redox electrolyte for increasing the dye-regeneration process upon photoexcitation. Accordingly, a set of unsymmetrical squaraine dyes with indoline and triazatruxene amine donor-based D-A-D dyes are designed (KV1-KV3), synthesized, and sensitized with a semiconducting metal oxide (TiO2) film. The sensitizer forms a monolayer on the TiO2 surface, leading to a dye-dye interaction, which broadens the absorption spectrum. The N atom of the triazatruxene amine donor was left unsubstituted in KV1, whereas a hexyl chain was installed in KV2 and KV3 and a branched alkyl chain was installed on the core N atoms in KV3 to control the self-assembly of dyes on the TiO2 surface. Self-assembly of alkyl groups wrapped in KV1-KV3 dyes on the TiO2 surface aids surface passivation and broadens the absorption profile, improving the light-harvesting capabilities. The DSSC devices based on KV2 exhibited a high power conversion efficiency of 7.85% (V-oc = 794 mV, J(sc) = 14.76 mA/cm(2), and FF = 67%), with an onset incident photon-to-current conversion efficiency response from 680 nm.
Keywords: aggregationof dyes; Dye-sensitized solar cells; metal-free organic dyes; self-assembly of dye; squaraine dyes; triazatruxene

Visible, far-red, and near-infrared active unsymmetrical squaraine dyes based on extended conjugation within the polymethine framework for dye-sensitized solar cells - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Alkyl group wrapped visible, far-red, and NIR active unsymmetrical squaraine dyes with pi-extension in the polymethine framework-based AM4-AM7 have been designed, synthesized, and utilized as sensitizers for dye-sensitized solar cells. To extend the pi-conjugation within the polymethine framework, thiophene moieties have been incorporated between the donor and acceptor moieties. Absorption spectroscopic studies revealed that pi-extension with each -C & boxH;C- unit resulted similar to 100 nm of redshift in the charge transfer transition with the lambda(maximum) of 541, 643, 747, and 833 nm for AM4, AM5, AM6, and AM7 dyes, respectively, with the molar extinction coefficient of >10(5) M(-1)cm(-1). The pi-extended conjugation-based AM6 and AM7 dyes showed improved light-harvesting efficiency (LHE), where the AM7 dye showed an LHE of 386 nm at 60%. Electrochemical studies of AM dyes revealed that the HOMO energy level of the sensitizers has been modulated systematically. Further, pi-extension within the polymethine framework showed a dramatic effect on V-OC, J(SC), and device efficiency when move from visible active AM4 to far-red active to NIR active AM7 dyes. The DSSC efficiencies of 7.35, 5.18, 0.08, and 0.053% have been achieved with the I-/I-3(-) electrolyte (Z-50) for the AM4, AM5, AM6, and AM7 dyes, respectively. Further, AM4 dye has been cosensitized with AM5, AM6, and AM7 dyes, where AM4:AM5 (1:1) composition achieved the maximum efficiency of 8.12% with I-/I-3(-) electrolyte (Z-50) compared to the other cosensitization compositions.
Keywords: aggregation of dyes; DSSC device efficiency; light-harvesting efficiency; pi-extension; polymethine framework; squaraine dyes

Double anchoring squaraine dye with triazatruxene amine donor for dye-sensitized solar cells: sequential cosensitization for panchromatic light-harvesting - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
Dyes are firmly bound to a semiconducting TiO2 film using carboxylic acid anchoring groups for an efficient electron transfer from the excited state of dye to the conduction band (CB) of TiO2. Strong dye binding can be accomplished with multi-anchoring dye designs to improve photophysical characteristics, including high extinction coefficients, panchromatic absorption, post-sensitization modifications, and dark current suppression, besides enhancing the stability of the dye-TiO2 interface. Herein, a novel KV2D dye with double squaraine acceptor and double carboxylic acid anchoring groups is designed to achieve a high extinction coefficient (epsilon, 3.57 x 105M-1cm-1) and robust binding to the TiO2 film for an effective electron transfer. We systematically changed the amount of coadsorbent chenodeoxycholic acid (CDCA) to control the aggregation of dyes on the TiO2 surface that improves the power conversion efficiency (PCE, eta) for the devices based on the doubleanchoring KV2D. Out of these devices, KV2D: CDCA (1:10) based cell exhibited the best PCE of 5.26% with VOC of 754 mV, JSC of 10.41 mA/cm2, and ff of 67%. The sequential cosensitization studies were carried out with a far-red active dye to find the effect of the strong binding of the sensitizer to the TiO2 film. Interestingly, when di-anchoring, KV2D was sensitized first for 12 h and then sequentially cosensitized with far-red absorbing SQS4 for 5 h to achieve a PCE of 5.0% with VOC of 697 mV, JSC of 10.23 mA/cm2, and ff of 70% with panchromatic spectral response in IPCE upto 730 nm giving higher photocurrent generation.
Keywords: aggregation of dyes; Bulky donor unit; Double acceptor dye; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

Effect of cyclization and alkyl group wrapping in visible-light-active unsymmetrical squaraine dyes for dye-sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Shivankar, Bhavana R.; Siby, Jesna; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
A series of alkyl group-appended indoline- and carboxylic acid-functionalized indolenine-based visible-light-active unsymmetrical squaraine dyes, SQA7-10, were designed, synthesized, and utilized for the dye-sensitized solar cells device fabrication. The number of alkyl group has been increased systematically on the indoline moiety to control the self-assembly of dyes on TiO2 and to passivate the photoanode that helps in improving the open-circuit voltage (V-OC) by avoiding the charge recombination process. SQA7-10 dyes showed an absorption between lambda(max) 536-540 nm, with molar extinction coefficients of 1.62-2.13 x 10(5) M-1 cm(-1) in CH3CN. Further, ultraviolet-visible (UV-vis) studies on TiO2 indicated the formation of H-aggregated dyes (505-510 nm), which can be controlled by appending the alkyl groups. The energy levels of the highest occupied molecular orbital (HOMO) of these dyes are well aligned with the Nernst potentials of I-/I(3)(-)electrolyte and [Cu(tmby)(2)](+/2+) electrolytes with sufficient overpotentials required for the dye regeneration process. DSSC devices made with these dyes showed systematic enhancements of open-circuit voltage (V-OC) and device efficiency with respect to alkyl group incorporation for SQA7-10 with I-/I-3(-) electrolytes. All of the SQA dyes exhibited the device V-OC of more than 805 mV, where the introduction of alkyl groups systematically enhanced the V-OC in the order of SQA7 (805 mV) < SQA8 (829 mV) < SQA9 (843 mV) < SQA10 (862 mV) without any addition of CDCA. Within the SQA dye series, SQA10 dye has achieved the highest DSSC device efficiency of 7.52% (J(sc) of 11.16 mA/cm(2), V-oc of 862 mV, and ff of 78%) with I-/I-3(-) electrolyte, whereas use of [Cu(tmby)(2)](+/2+) redox shuttle with SQA10 showed enhanced V-oc (1080 mV) and device efficiency (8.35%). The IPCE profile for the device fabricated with SQA dyes showed good response at 480 and 560 nm, which indicates the photocurrent generation from the aggregated structures.
Keywords: aggregation of dyes; charge recombination; Dye-sensitized solar cells; indoline and indolenine donors; visible-light-activeunsymmetrical squaraine dye

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye

Squaraine dyes as efficient photoredox catalysts for PET-RAFT polymerization in batch and flow modes accelerated by suppression of dye aggregation - Patil, Anil M.; Nawghare, Indrajeet S.; Nithyanandhan, Jayaraj; Ambade, Ashootosh V. (Macromolecules, 2025)
Organic photoredox catalysts (PCs) based on squaraine dyes are investigated for photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization under visible-light (lambda max = 485 nm) irradiation in the presence of triethylamine that suppresses self-aggregation of dye and accelerates the polymerization. Several commonly used PCs are also screened, and self-aggregation is found to be reduced with triethylamine, thus providing a simple and effective approach to reduce aggregation of PCs. There is no induction period, and total polymerization time is shorter for squaraine dye PCs than for reported PCs under similar conditions. The photocatalyst system is amenable to polymerization by using different RAFT agents. Methyl methacrylate and a range of functional methacrylates are polymerized with good control over molecular weight and narrow dispersity in a first-order reaction with a random switch ``ON-OFF'' of the light source and even without an inert atmosphere. The mechanism of polymerization without and with requirement of triethylamine is elucidated using control experiments and found to be an oxidative and reductive electron transfer, respectively. A series of diblock and random copolymers of methyl methacrylate with methacrylate monomers are synthesized. Controlled polymerization is also demonstrated using a continuous-flow method and in an aqueous medium.

Visible-light active π-extended unsymmetrical squaraine dyes for dye-sensitized solar cells: steric effects for controlling the aggregation of dyes - Jadhav, Avinash P.; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
The dye-anchored TiO2 photoanode plays a vital role in the light harvesting and charge separation processes in dye-sensitized solar cells. Aggregation of dyes (H- and J-type) on the TiO2 surface is a facile process due to the presence of a periodical dye anchoring sites on the exposed facet of titania, and such self-assembled dye structures help broadening the absorption profile. However, photocurrent generation from such aggregated structure is a challenging task in dye-sensitized solar cell devices. Hence, controlling the dye aggregation on the TiO2 surface is an important aspect. Controlling the aggregation of dyes by which (i) an enhanced photocurrent generation (J SC) and (ii) enhanced V OC can be achieved by including the steric factors to the dye design principles, the steric factor in the sensitizer may help passivate the TiO2 surface to avoid the charge recombination process between electrons present in TiO2 and the oxidized electrolyte. On the other hand, extension of pi-conjugation in a sensitizer helps enhance the light absorption in the visible region besides modulating the HOMO and LUMO energy levels. Hence, synergizing both pi-extensions along with features that control the dye aggregation has been considered in designing visible active squaraine dyes. A thiophene pi-spacer was inserted in between a visible-light active unsymmetrical squaraine unit and a cyanoacetic acid acceptor unit to provide the AJ1 and AJ2 dyes. Though both the dye molecules possess a similar pi-framework, the AJ2 dye was functionalized with both in-plane and out-of-plane alkyl groups to decrease the aggregation of dyes on the TiO2 surface compared to AJ1. The AJ1 and AJ2 dyes absorbed at 560 nm with shoulder peaks appeared at 528 nm, which can be assigned to vibronic progression (1082 cm-1), and additional characteristic peaks of thiophene appeared at 392 nm with the molar extinction coefficient of 1.16-1.19 x 105 M-1 cm-1 in CH3CN. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of iodolyte (I-/I3 -) electrolyte with sufficient overpotentials for charge injection and dye regeneration processes, respectively. The highest DSSC device efficiency of 7.37% (J SC 14.44 mA/cm2, V OC 0.771 V, ff 67.1%) was achieved for the AJ2 dye with iodolyte (I-/I3 -) electrolyte in the presence of 2 equiv of optically transparent coadsorbent chenodeoxycholic acid (CDCA), which showed a good IPCE response in between 400 and 700 nm. Further, cosensitization of visible-light active AJ1, AJ2, and SQA10 dyes with a complementary far-red active SQS4 dyes showed the device efficiencies of 5.53% (AJ1:SQS4:CDCA), 7.14% (AJ2:SQS4:CDCA), and 7.18% (SQA10:SQS4:CDCA) with a good IPCE response in the 400-720 nm region.
Keywords: cosensitization; Dye aggregation; Dye-sensitized solar cells; pi-extended squaraine dye; visible-lightactivedyes

Auxiliary triazatruxene donor-based squaraine dyes for dye-sensitized solar cells: cis- and trans- configuration of dyes for modulating photophysical and electronic properties - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemistry-an Asian Journal, 2026)
In DSSCs, dye regeneration efficiency and dye aggregation on the TiO2 surface can be modulated by using bulky aromatic donors wrapped with alkyl groups. Introduction of rigid aromatic rings around the donor unit of a dye will directly impact the driving force for electron injection and dye regeneration of a dye. In this work, we designed and synthesized KNS dyes with an auxiliary TAT donor integrated with a visible active squaraine dye. Here, octupolar-structured auxiliary TAT wrapped with alkyl groups is used as a strong donor and shelter to reduce the dye aggregation and charge recombination process. Further, to improve the light-harvesting efficiency and incident photon-to-current conversion efficiency of DSSC devices fabricated with KNS dyes, the central squaric acid unit has been modified by appending the electron-withdrawing dicyano group at the central squaric unit, and the trans-configured KNS1 dye was converted to cis-configured KNS2 dye. The power conversion efficiency of devices based on the KNS dyes was studied with and without 3 equivalents of CDCA by using the I-/I3 - electrolyte. Out of these devices, the KNS1: CDCA (1:3) based cell exhibited the best PCE of 6.25% with V OC of 793 mV, J SC of 11.08 mA cm-2, and ff of 71%.
Keywords: Bulky donor unit; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

D-A-D based NIR and visible homodimeric squaraine dyes for dye-sensitized solar cells: Modulation of excitonic coupling - Siby, Jesna; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2026)
Dye-TiO2 interface plays a crucial role in the overall performance of dye-sensitized solar cells. Anchoring groups help to bind the dye on TiO2 and inject the electrons to the conduction band of TiO2. In this work, a series of homodimeric NIR squaraine dyes C6NIR, C10NIR, and visible squaraine dyes C6VIS, C10VIS are designed and synthesised. These dimeric dyes are covalently connected by decyl or hexyl units between the nonanchoring side of their monomeric unit. Optical spectroscopy in solution and on TiO2 surface indicates that the excitonic coupling between the dyes can be modulated. All the dimeric dyes showed better photovoltaic performance than their corresponding monomeric dyes. The dyes showed device performance SQ1 (1.28%) < C6NIR (2.26%) < C10NIR (2.79%) and AK2 (3.59%) < C6VIS (4.34%) < C10VIS (5.28%) respectively. The dimeric dyes showed better light harvesting efficiency and better passivation of the TiO2 surface. It helps to enhance the device's overall performance by improving the photocurrent and open circuit voltage. The decyl-linked dimeric dyes showed better performance among this set of dyes and C10NIR dyes showed V-oc of 614 mV, J(sc) of 7.08 mA/cm(2), and ff of 64.2%. and C10VIS showed V-oc of 724 mV, J(sc) of 10.74 mA/cm(2), and ff of 67.9%.
Keywords: charge recombination; Dye aggregation; Dye-sensitized solar cells; Dye-TiO2 interface; squaraine dyes; surface passivation

pH-Responsive and antimicrobial polymer synthesis in continuous flow and effect of pendant alkylamine on the squaraine dye photocatalyst activity - Patil, Anil M.; Nawghare, Indrajeet S.; Siby, Jesna; Bankar, Priyanka M.; Dastager, Syed G.; Rode, Chandrashekhar V.; Nithyanandhan, Jayaraj; Ambade, Ashootosh V. (ACS Applied Polymer Materials, 2026)
pH-responsive and antimicrobial polymers were synthesized by photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization under blue light (lambda max = 485 nm) using a scalable continuous flow method. The effect of pendant alkylamino groups with different alkyl substituents on methacrylate monomers under blue light is investigated in the absence of a tertiary alkylamine reagent and in the presence of cyanopentanoic acid dithiobenzoate and 4-cyano-4-[(dodecylsulfanylthiocarbonyl) sulfanyl]pentanoic acid as RAFT agents. The rate of polymerization is found to vary with the size of the alkyl chain and with the tertiary, secondary, or quaternary nature of the amino group. The ability of pendant alkylamino groups to transfer electrons to the photocatalyst is shown using cyclic voltammetry and fluorescence quenching experiments; the tendency to suppress dye aggregation is observed using UV-vis spectroscopy; and the rates of polymerization could be correlated with the trend in these results. The mechanism of polymerization is proposed to follow a reductive or oxidative electron transfer pathway depending on the nature of the pendant group. Statistical and diblock copolymers with 2-hydroxyethyl methacrylate are synthesized in batch and continuous flow processes with a comparative study of kinetics in the two methods. The synthesis of high-molecular-weight homopolymer (55,000 g/mol) and statistical copolymer (85,000 g/mol) of N,N-diisopropylaminoethyl methacrylate is shown in continuous flow. The solution self-assembly of diblock copolymers is studied, and the pH-responsive morphology change leading to disassembly is shown. The antimicrobial properties of polymers with a quaternary ammonium pendant group are evaluated. The thermal degradation of statistical copolymers is analyzed.
Keywords: alkylaminoethyl methacrylate; Antimicrobial; continuous flowprocess; PET-RAFT; pH-responsive; self-aggregation